Promising protective potential of MiR-103a-3p against polystyrene microplastic neurotoxicity in rats - Mohammadi, Leila; Baluchnejadmojarad, Tourandokht; Goudarzi, Mina; Khodashenas, Vahid; Khoshravesh, Roya; Roghani, Mehrdad (Frontiers in Toxicology, 2025)
Introduction: Microplastics are ubiquitous environmental pollutants with potential neurotoxic effects that can impair learning and memory. MicroRNAs are essential regulators of a number of physiological and pathological processes, but detailed information on the impact of miRNAs on the neurotoxic effects of microplastics is lacking.Methods: In the present study, polystyrene microplastics (PS-MPs) were administered orally and miR-103a-3p was injected intracerebroventricularly as a treatment for PS-MPs-induced neurotoxicity.Results and Discussion: Performance in the novel object discrimination Y-maze and Barnes maze tests indicated that miR-103a-3p mitigates the deleterious effects of PS-MPs on learning and memory. Oxidative stress, pyroptosis, apoptosis and inflammation induced by PS-MPs were modulated after miR- 103a-3p injection by reducing malondialdehyde, protein carbonyl, nitrite, caspase 3, caspase 1, TNFα, and NLRP3 levels in hippocampal tissue. Our results also showed that miR-103a-3p can reverse the impact of PS-MPs on astrocytic reaction and SIRT1 and BDNF levels. MiR-103a-3p alleviated PS-MPs-induced endoplasmic reticulum (ER) stress through reducing the levels of PERK, CHOP and GRP78. These findings imply that miR-103a-3p exerts a neuroprotective influence against cognitive deficits induced by exposure to PS-MPs. This is achieved by reducing inflammation, oxidative stress, apoptosis and endoplasmic reticulum stress.